Effects of dispersion and deformation histories on rheology of semidilute and concentrated suspensions of multiwalled carbon nanotubes - Kucuk, Ilknur; Gevgilili, Halil; Kalyon, Dilhan M. (JOURNAL RHEOLOGY AMER INST PHYSICS, 2013)
A new sonication method involving in situ measurement of electrical conductivity along with the characterization of dynamic properties was developed to better control the dispersion of multiwalled carbon nanotubes (CNTs) in polymeric liquids. Using this new method, CNTs were incorporated into monoacrylate-terminated poly(ethylene glycol) at CNT volume fractions, phi, in the semidilute (3.7 x 10(-4) and 5.5 x 10(-3)) and concentrated (1.1 x 10(-3), 1.6 x 10(-3) and 2.7 x 10(-3)) regimes. This dispersion methodology enabled the preparation of stable CNT suspensions, with reproducible electrical conductivity and dynamic properties, to serve as specimens for subsequent steady and oscillatory shear, and compressive squeeze flows that were carried out in combination with optical imaging and continuous monitoring of their electrical conductivity. During small-amplitude oscillatory shear, the networks established by well-dispersed CNTs remained stable, as evidenced by optical imaging and constant values of electrical conductivity and dynamic properties. The demixing of CNTs and formation of flocculates upon stacking of the CNTs into helical bands in the vorticity direction occurred over a wide range of CNT concentrations, apparent shear rates, and rheometer gaps during steady torsional and cone-and-plate flows and gave rise to precipitous decreases in electrical conductivity, dynamic properties, shear viscosity, and first normal stress difference (which reached negative values). On the other hand, electrical conductivity and dynamic properties were observed to increase modestly during squeeze flow, which occurred free of the strong demixing effects observed in simple shear flows. Regardless of the type of deformation, quiescent relaxation following deformation gave rise to the increase of electrical conductivity and dynamic properties to asymptotic values. Overall, these findings shed additional light into the percolating network formation and associated viscoelastic behavior and electrical conductivity of CNT suspensions and demonstrate the significant sensitivities of their ultimate properties to their preparation and subsequent deformation histories. (C) 2013 The Society of Rheology.
Keywords: SQUEEZE FLOW; ELECTRICAL-CONDUCTIVITY; PERCOLATION THRESHOLDS; WALL SLIP; NANOCOMPOSITES; BEHAVIOR; PARAMETERS; MICROSTRUCTURE; COMPOSITES; SONICATION; Mechanics